How to Find Molecules with Long-lasting Charge Migration? - Alan Scheidegger; Nikolay V. Golubev; Jiří Vaníček (CHIMIA, 2023)
Under certain conditions, the ionization of a molecule may create a superposition of electronic states, leading to ultrafast electron dynamics. If controlled, this motion could be used in attochemistry applications, but it has been shown that the decoherence induced by the nuclear motion typically happens in just a few femtoseconds. We recently developed an efficient algorithm for finding molecules exhibiting long-lasting electronic coherence and charge migration across the molecular structure after valence ionization. Here, we first explain why the but-3-ynal molecule is a promising candidate to study this type of ultrafast electron dynamics. Then, we use the 3-oxopropanenitrile molecule, which does not induce long-lasting charge migration in any of three different ionization scenarios, as an example demonstrating that several different properties must be fulfilled simultaneously to make the attochemistry applications possible.